Re-thinking social protection: From poverty alleviation to building resilience in middle-income households - Diego Alejandro Vera Cossío; Bridget Hoffmann; Camilo Pecha; Jorge Gallego; Marco Stampini; David Vargas; María Paula Medina; Esteban Alvarez (Inter-American Development Bank (IDB), 2023)
We exploit an expansion in social protection to middle-income households to provide evidence on how middle-income households cope with economic shocks and how to build their resilience. We use a regression discontinuity design around the eligibility cutoff for a program that delivered monthly cash transfers mainly through bank accounts in Colombia. We find no impacts on food security, education, and health outcomes-the target outcomes of antipoverty programs. In contrast, program eligibility increases non-food consumption and reduces debt for routine expenses. Bank account ownership increases by 16%, and beneficiaries are more likely to borrow from formal lenders. Amid systemic and idiosyncratic shocks, the program prevents middle-income households from reducing non-food spending and acquiring debt for routine expenses. Moreover, when hit by severe shocks, beneficiary households substitute away from predatory loans. The results suggest that middleincome households are constrained by lack of insurance and that social protection can build middle-income households' resilience to shocks through both cash transfers and by integrating beneficiaries into formal credit markets.
Keywords: I18; I38; O15; 330; Basic income; Insurance; Cash transfers